Capsaicin - Sensitive Neural Afferentation and the Gastrointestinal Tract from Bench to Bedside - Mozsik, Gyula; Abdel- Salam, Omar M. E.; Takeuchi, Koji (IntechOpen, 2014)
The capsaicin, a component of paprika, has been used in the culinary practice of every day nutritional practice. This agent is known to cause a variety of actions in the body through activating capsaicin-sensitive afferent neurons. A recently launched book entitled, Capsaicin-Sensitive Neural Afferentation and the Gastrointestinal Tract: from Bench to Bedside, is attractive for several reasons. First, Prof. Mozsik, a chief editor of this book, is known internationally as an expert in capsaicin pharmacology. Since he has worked for many years as a head of internal medicine, taking care of patients with various GI diseases, he is able to make a correct interpretation of various findings obtained in basic researches to clinical events. Second, although there are many articles about capsaicin, they mostly deal with basic research and finding but do not include much about clinical finding. Third, this book encompassed review articles written by internationally accepted scientists leading the field of capsaicin research, who highlighted the current state of knowledge on pharmacology, physiology and clinical phathophysiology of capsaicin-sensitive afferent neurons, and discussed directions for future research. Overall, this book is for people who are interested in the capsaicin action in body.